Assessment of spread and distribution pattern of contrast dye injected under ultrasound guidance in the transverse abdominal plane. A cadaveric study - Chesov, I. I. (Pain medicine, 2017)
Optimal volume and concentration of injected local anesthetic, as well as sensory block extension remain controversial in case of TAP-block. The aim of the present study was to assess the extent and the pattern of dye (methylene blue) spread, injected in the transverse abdominal plane on fresh unfixed cadavers. Methods. The study was conducted on 15 fresh unembalmed. Cadavers were randomly assigned into 3 equal groups, depending on the amount of dye injected into transverse abdominal area (10, 20 and 40 ml). An ultrasound-guided injection of dye (methylene blue 1 %) into the TAP plane was performed for each hemi-abdominal wall. The extent of spread within the TAP plane was determined by detailed dissection of the hemi-abdominal wall. The craniocaudal and mediolateral distribution of dye was assessed for every single cadaver bilaterally. Results. The results of present cadaveric study demonstrate significant differences in the dye distribution after injection of 10 ml methylene blue in the transverse abdominal plane, compared with 20 to 40 ml of contrast dye (p < 0.001). At the same time, there were no significant differences in the distribution of the craniaocaudal and mediolateral spread of dye after injection of 20 and 40 ml into the transverse abdominal area (p > 0.05). A strong positive correlation was found between the cephalocaudal and mediolateral extent of methylene blue and the volume of dye injected in the transverse abdominal area. Conclusion. Our results suggest that 20 ml of contrast dye injected into transverse abdominal space provide significant larger spread in craniocaudal and mediolateral distance than the volume of 10 ml. At the same time, the spread of contrast dye was similar for volumes of 20 and 40 ml. The 20 ml may be an optimal volume of local anesthetics used for TAP-block.